Terrestrial exospheric hydrogen density distributions under solar minimum and solar maximum conditions observed by the TWINS stereo mission - J. H. Zoennchen; U. Nass; H. J. Fahr (Annales Geophysicae, 2015)
Circumterrestrial Lyman-α column brightness observations above 3 Earth radii (Re) have been used to derive separate 3-D neutral hydrogen density models of the Earth's exosphere for solar minimum (2008, 2010) and near-solar-maximum (2012) conditions. The data used were measured by Lyman-α detectors (LAD1/2) onboard each of the TWINS satellites from very different orbital positions with respect to the exosphere. Exospheric H atoms resonantly scatter the near-line-center solar Lyman-α flux at 121.6 nm. Assuming optically thin conditions above 3Re along a line of sight (LOS), the scattered LOS-column intensity is proportional to the LOS H-column density. We found significant differences in the density distribution of the terrestrial exosphere under different solar conditions. Under solar maximum conditions we found higher H densities and a larger spatial extension compared to solar minimum. After a continuous, 2-month decrease in (27 day averaged) solar activity, significantly lower densities were found. Differences in shape and orientation of the exosphere under different solar conditions exist. Above 3 Re, independent of solar activity, increased H densities appear on the Earth's nightside shifted towards dawn. With increasing distance (as measured at 8Re) this feature is shifted westward/duskward by between −4 and −5° with respect to midnight. Thus, at larger geocentric distance the exosphere seems to be aligned with the aberrated Earth–solar-wind line, defined by the solar wind velocity and the orbital velocity of the Earth. The results presented in this paper are valid for geocentric distances between 3 and 8Re.